Synergistic aspects of dual education in Hungarian universities - Veres Somosi, Mariann; Nagy, Szabolcs; Pererva, P. G. (Хмельницький національний університет, 2025)
The study examines the synergistic aspects of dual education in Hungarian universities, focusing on the integration of academic learning with practical industry training. Dual education provides students with the opportunity to combine theoretical knowledge with hands on experience in enterprises, thereby strengthening their professional competencies and employability. The synergy arises from close collaboration between universities and industry partners, which enhances curriculum relevance, fosters innovation, and supports the development of a skilled workforce aligned with labor market needs. The paper highlights the benefits of this model for students, universities, and employers, while also addressing challenges related to implementation and sustainability.
Keywords: dual education; Hungarian universities; university industry collaboration; practical training; employability; innovation; workforce development